Isothermal Decay Analysis of Thermoluminescence Peaks of Nano-α-Alumina - Ahadov, Ahmad; Mammadov, Sahib; Gurbanov, Muslim; Abishov, Aqshin; Ahadova, Aybeniz (Physics and Chemistry of Solid State, 2024)
This study investigates the thermoluminescence (TL) behavior of nano α-Al2O3 (40 nm) within the temperature range of 110 to 160°C to elucidate the kinetic mechanisms governing its TL response. The isothermal decay curves were analyzed to determine the order of kinetics and activation energies of the TL peaks. The ln(I) vs. time plot revealed a nonlinearity starting at 140°C, indicating that the TL peaks do not follow first-order kinetics in this temperature region. Subsequent analysis confirmed that the TL data align with second-order kinetics, with a kinetic-order parameter of b = 2.0 providing the best linear fit. Further examination of the ln(slope) vs. 1/kT relationship revealed a composite structure in the TL response, characterized by three distinct linear sections. These sections correspond to activation energies of 0.6±0.12 eV, 1.07±0.25 eV, and 1.61±0.47 eV, respectively, suggesting the presence of three different centers contributing to the dosimetric peak. The findings underscore the complex nature of the TL response in nano α-Al2O3, highlighting the necessity of considering multiple kinetic components in the analysis of its TL properties. This study enhances our understanding of the thermoluminescent behavior of nano α-Al2O3 and provides a basis for further research into its applications in dosimetry